Performance of ozonation on bisphenol a degradation: Efficiency, mechanism and toxicity control - Han, Qi; Dong, Wenyi; Wang, Hongjie; Yu, Boping; Dong, Zijun; Li, Mu; Xie, Linshen; Dai, Zhiguang (Frontiers in Environmental Science, 2022)
In this study, the degradation of bisphenol A (BPA) by ozonation was studied systematically by investigating the effects of different factors, including ozone dosages (0.25~1.50 mg/L), temperatures (10~50 °C), initial solution pH (3.0~11.0) and interfering ions. The reaction kinetics were analyzed at the same time. In addition, the generation of intermediates was analyzed and the possible mechanism was proposed by combining with the density functional theory calculation. At last, the variation and controlling effect of toxicity was also evaluated. The results showed that ozone had a stronger degrading ability of BPA (1.0 mg/L), complete removal rate was obtained within 10 min when dosing only 1.0 mg/L ozone. The BPA degradation reactions were well fitted with pseudo-second-order kinetics and could well adapt with the wide range of pH (3.0-9.0), during which over 91% removal of BPA was observed. The indirect pathway by ·OH oxidation was proved mainly responsible for BPA degradation by the scavenging experiments. HCO3-, NH4+ and humic acid showed a certain inhibiting effect. Fe3+ and Cu2+ played a catalytic role on BPA degradation. The DFT calculation has identified the reactive regions in terms of radical (F•) and electrophilic attack (F-), revealing that attack would be initiated on the aromatic ring and olefinic double bonds. Thus, combining the results of DFT with GC/MS-MS detection, two degradation pathways of BPA were proposed. Toxicity evaluation showed that, due to the generation and accumulation of more toxic intermediates, values of T% had a sharp increase at initial stage. However, with ozone dosage increasing to 1.50 mg/L, the toxicity could be effectively controlled much lower (5%) than BPA itself (49%).